Therapeutic strategies in gastroparesis: Results of stepwise approach with diet and prokinetics, Gastric Rest, and PEG‐J: A retrospective analysis. Issue 6 (4th April 2019) - Strijbos, Denise; Keszthelyi, Daniel; Smeets, Fabiënne G. M.; Kruimel, Joanna; Gilissen, Lennard P. L.; de Ridder, Rogier; Conchillo, José M.; Masclee, Ad A. M.
Abstract: Background: Gastroparesis is characterized by abnormal gastric motor function with delayed gastric emptying in the absence of mechanical obstruction. In our tertiary referral center, patients are treated with a stepwise approach, starting with dietary advice and prokinetics, followed by three months of nasoduodenal tube feeding with "gastric rest." When not successful, a percutaneous endoscopic gastrostomy with jejunal extension (PEG‐J) for long‐term enteral feeding is placed. Aim: To evaluate the effect of this stepwise approach on weight and symptoms. Methods: Analyses of data of all referred gastroparesis patients between 2008 and 2016. Key Results: A total of 86 patients (71% female, 20‐87 years [mean 55.8 years]) were analyzed of whom 50 (58%) had adequate symptom responses to diet and prokinetics. The remaining 36 (decompensated gastroparesis) were treated with three months gastric rest. Symptom response rate was 47% (17/36). Significant weight gain was seen in all patients, independent of symptom response. In the remaining 19 symptom non‐responders, the enteral feeding was continued through PEG‐J. Treatment was effective (symptoms) in 37%, with significant weight gain in all. In 84% of patients, the PEG‐J is still in use (mean duration 962 days). Conclusions and Inferences: Following a stepwise treatment approach in gastroparesis, adequate symptom response was reached in 86% of all patients. Weight gain was achieved in all patients, independent of symptom response. Diet and prokinetics were effective with regard to symptoms in 58%, temporary gastric rest in 47%, and PEG‐J as third step in 37% of patients. Abstract : Symptom management of gastroparesis is challenging, due to an incomplete understanding and limited therapeutic options. About 30% of patients eventually need enteral feeding. Following a stepwise treatment approach (including diet and prokinetics, Gastric Rest, PEG‐J) in gastroparesis, adequate symptom response was reached in 86% of all patients, whereas weight gain was achieved in all patients, independent of symptom response.